Legal certainty of internal regulations in health services in government hos-pitals - Suryaningdiah, Daniek; Subekti, Subekti; Suyono, Yoyok Ucuk; Sidarta, Dudik Djaja (LEGAL BRIEF, 2025)
The purpose of this study is to analyze and find out that Internal Regulations (Hospital ByLaws) in government hospitals in Indonesia meet the principles of legal certainty and harmonization between Internal Regulations (Hospital ByLaws) as well as higher regulations in the legal system related to health services in government-owned hospitals. The type of research applied is normative legal research using a statutory approach, a conceptual approach, and a comparative approach. The results of the analysis show that the inconsistency between Internal Regulations (Hospital ByLaws) and regulations that have a higher hierarchy can produce various legal consequences, such as decreased hospital accreditation, lawsuits from patients or medical personnel, and the risk of administrative sanctions. Thus, the hospital must carry out continuous evaluation and revision to ensure compliance with the latest regulations. Disagreements that are left can cause legal losses for both hospitals, medical personnel, and patients. Hospitals are at risk of losing accreditation, facing lawsuits, and experiencing administrative issues that can disrupt operations. In addition, inconsistencies can also disrupt public trust in the hospital